Correlations between objective and subjective sleep and circadian markers in remitted patients with bipolar disorder. (June 2014) - Boudebesse, Carole; Geoffroy, Pierre Alexis; Bellivier, Frank; Henry, Chantal; Folkard, Simon; Leboyer, Marion; Etain, Bruno
<x xml:space="preserve">Abstract</x> Bipolar disorder (BD) is a chronic psychiatric condition characterized by recurrences of depressive and (hypo)manic episodes. Patients in remission report a wide range of sleep and circadian disturbances that correlate with several outcomes measures such as functioning or physical health. The most appropriate way to measure these abnormalities in clinical practice requires further investigation since the external validity of self-reports, as compared to more physiological measures (such as polysomnography or actigraphy), has been questioned. Despite the fact that questionnaires are inexpensive, fast and easy to use, they need to be validated against objective measures. This study aims to validate three sleep and circadian questionnaires, namely the Pittsburgh Sleep Quality Index (PSQI), the Composite Scale of Morningness (CSM) and the Circadian Type Inventory (CTI) – against actigraphy in BD patients in remission. Twenty-six carefully assessed BD patients in remission completed the PSQI, the CTI and the CSM, and wore an actigraph (AW7, Camntech) for 21 consecutive days. Phase preference assessed by the CSM strongly correlated with actigraphic phase markers (M10 onset ρ = −0.69 and L5 onset ρ = −0.63). Sleep duration and sleep latency assessed by the PSQI and by actigraphy were also highly correlated (ρ = −0.76; ρ = 0.50). Moderate correlation coefficients were observed between questionnaires and actigraphy for markers that explored the stability of rhythms, sleep quality, sleep latency and sleep disturbances (|ρ| > 0.40) although these were not significant after correcting for multiple testing. No correlation was observed between markers for the amplitude of rhythms. While the external validity of the CTI clearly requires further investigation, this study supported the external validity of the CSM and the PSQI for phase preference, sleep duration and latency. We conclude that the CSM and the PSQI could be useful in routine practice and research when actigraphy is not easily available.